Richard Hooker: beyond certainty - Russell, Andrea (2010)
For over four hundred years Richard Hooker has been firmly attached to the Church of England and his life and writings used to promote and preserve that institution’s self-understanding. Consensus as to his theological beliefs and ecclesiastical loyalties has, however, never been reached – even though each generation of scholars has claimed to discover the 'real' Richard Hooker. In spite of the differing, and often conflicting interpretations, there have been several constants – beliefs about Hooker and his work that have remained virtually unchallenged throughout the centuries. The aim of this thesis has been to examine three of those aspects and in so doing ascertain whether their truth is more assumed than proven. The first of these assumptions is the fundamental belief that Hooker is attached securely to the English Church and that their identities are so interwoven that to speak of one is to speak of the other. The second is that Hooker’s prose – his unique writing style and powerful rhetoric – can be ignored in the process of determining his theology. And thirdly, the widely-held belief that, as the 'champion of reason', Hooker’s faith is essentially rational and that God is perceived and experienced primarily through the intellect. Challenging the truth of each of these statements leads to an uncertainty about Hooker that, rather than negating scholarship, allows research to be liberated from the dominance of categorisation. Such a change would acknowledge that Hooker's theology transcends Anglican studies and would allow his radical thinking to reach a wider audience.